1970
DOI: 10.1083/jcb.45.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Mitochondria Isolated From Neuron-Enriched and Glia-Enriched Fractions of Rabbit and Beef Brain

Abstract: Fractions enriched in neuronal and glial cells were obtained from dispersions of whole beef brain and rabbit cerebral cortex by large-scale density gradient centrifugation procedures. The fractions were characterized by appropriate microscopic observation. Mitochondria were then isolated from these fractions by differential centrifugation of their homogenates. The two different types of mitochondria were characterized with respect to certain enzyme activities, respiratory rate, rate of protein synthesis, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…We also observed that not all mitochondria within MNs contained CyPD, ANT, and VDAC. This observation supports that idea of that mitochondria are heterogeneous in shape (Collins and Bootman, 2003; Jensen, 2005) and biochemical composition, notably metabolism (Hamburger et al, 1970), CyPD content (Naga et al, 2007), and genetics (Wallace, 2005). …”
Section: Discussionsupporting
confidence: 89%
“…We also observed that not all mitochondria within MNs contained CyPD, ANT, and VDAC. This observation supports that idea of that mitochondria are heterogeneous in shape (Collins and Bootman, 2003; Jensen, 2005) and biochemical composition, notably metabolism (Hamburger et al, 1970), CyPD content (Naga et al, 2007), and genetics (Wallace, 2005). …”
Section: Discussionsupporting
confidence: 89%
“…Thus, differences in the levels of individual mPTP components cannot explain the intrinsic differences in the sensitivity to Ca 2+ -induced permeability transition seen in spinal cord and brain isolated mitochondria [147, 148]. Not all mitochondria within individual MNs contained CyPD, ANT, and VDAC [78]; this observation supports that idea of that mitochondria in individual cells are not only heterogeneous in shape [149,150] but also in biochemical composition, notably metabolism [151] and genetics [36]. …”
Section: The Mitochondrial Permeability Transition Pore Contributementioning
confidence: 79%
“…Thus, differences in the levels of individual mPTP components cannot explain the intrinsic differences in the sensitivity to Ca 2+ -induced mPT seen in isolated mitochondria from spinal cord and brain [83,84]. Not all mitochondria within individual motor neurons contain CyPD, ANT, and VDAC [81]; this observation supports the idea that mitochondria in individual cells are not only heterogeneous in shape [85,86] but also in biochemical composition, metabolism [87] and genetics [8]. …”
Section: Types Of Cell Deathmentioning
confidence: 86%